Development of Cloud-Based Data Integration for Non-Profit Organization System - Mychael Maoeretz Engel; Yuwono Marta Dinata; Tony Antonio (Universitas Ciputra Surabaya, 2023)
Palang Merah Indonesia (PMI) noted that the stock of blood in Indonesia reached 87,238 bags as of June 14, 2022, where it should be estimated that Indonesia needs 5.1 million bags of blood every year. The conventional blood donor process procedure is one of the main reasons the younger generation does not intend to donate blood. A new system is needed to regulate the flow of the blood donation process so that it is faster and attracts the interest of young people to donate blood. This research resulted in a blood donation system in the form of a website application for each blood donor unit and a mobile application for users who are blood donors. The system was developed with the Agile method which makes it easy for researchers to adapt to the evolving needs of users. The system usability test is based on Nielsen's Criteria which includes 5 main aspects, including learnability, efficiency, memorability, errors and satisfaction. The results of the trial on the targeted respondents showed that almost all of them were interested in using and would routinely donate blood with the new system that had been built, because it was considered to simplify the blood donation procedure which was previously considered complicated. In addition, data between blood donor units can be well integrated with the system that has been built. In the end, this research has the main goal of changing people's habits, especially young people to continue to regularly donate blood, not only is it good for health, but also can help others in need.